2019
DOI: 10.1111/vsu.13178
|View full text |Cite
|
Sign up to set email alerts
|

Gait and electromyographic alterations due to early onset of injury and eventual rupture of the cranial cruciate ligament in dogs: A pilot study

Abstract: Objective: Identify relevant electromyography (EMG), kinematic, and kinetic changes resulting from monopolar radiofrequency energy (MRFE)-induced cranial cruciate ligament (CCL) injury and eventual rupture in dogs. Study design: Experimental, repeated measures. Animals: Five purpose-bred female dogs free of orthopedic and neurologic disease. Methods: Surface EMG, joint kinematics, and ground reaction forces were assessed at a trot in the pelvic limbs at baseline, at 2 and 4 weeks after unilateral MRFE-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…All loads in this model were applied directly and constantly throughout the joint angle range, although muscle loading in vivo involves complex patterns of co‐contraction with constantly varying loads and ratios, which were beyond the scope of this study. Although electromyography (EMG) data exist for some of the relevant muscles, 35 muscle forces do not always correlate well with EMG activity, being dependent on whether contraction is concentric, isometric, or eccentric 36 . However, the loads applied were sufficient to cause CTT and to demonstrate the positive effects of hamstring muscle activity on stifle stability.…”
Section: Discussionmentioning
confidence: 99%
“…All loads in this model were applied directly and constantly throughout the joint angle range, although muscle loading in vivo involves complex patterns of co‐contraction with constantly varying loads and ratios, which were beyond the scope of this study. Although electromyography (EMG) data exist for some of the relevant muscles, 35 muscle forces do not always correlate well with EMG activity, being dependent on whether contraction is concentric, isometric, or eccentric 36 . However, the loads applied were sufficient to cause CTT and to demonstrate the positive effects of hamstring muscle activity on stifle stability.…”
Section: Discussionmentioning
confidence: 99%
“…A positive outcome for orthopaedic disorders is dependent on optimal return to normal muscle function. One of the most common orthopaedic disorders causing lameness in dogs is cranial cruciate ligament disease (CCLD) ( 1 5 ). In CCLD, the function of the skeletal muscles is particularly challenged, as the normal stabilising synergism between the large muscles around the canine stifle joint and the cruciate ligaments is disrupted ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common orthopaedic disorders causing lameness in dogs is cranial cruciate ligament disease (CCLD) ( 1 5 ). In CCLD, the function of the skeletal muscles is particularly challenged, as the normal stabilising synergism between the large muscles around the canine stifle joint and the cruciate ligaments is disrupted ( 1 ). It has been found that the extension and flexion angles of surgically treated CCLD stifles are inferior to healthy joints, and that the active range of motion is impaired in the surgically treated limb at long-term assessment ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dogs naturally bear approximately two thirds of their weight on their forelimbs; thus, representing the brunt of musculoskeletal development and engagement during normal physical activity (3,4). The uneven distribution of weight along with common hip and spinal anomalies may impact muscle development and maintenance of the hindlimbs and core, predisposing these areas to injury or degenerative changes during moderate and vigorous activities encountered in the majority of working dog careers (5)(6)(7). Development of a dog's musculoskeletal system in the optimal biomechanical alignment through whole body proprioception, muscle stability and strength of the core, forelimbs, and hindlimbs, and mobility may decrease a dog's susceptibility to, the severity of, or the recovery time for an injury.…”
Section: Foundational Fitnessmentioning
confidence: 99%